1978
DOI: 10.1111/j.1365-2141.1978.tb05816.x
|View full text |Cite
|
Sign up to set email alerts
|

IgM Inhibitors of the Contact Activation Phase of Coagulation in Chlorpromazine‐ Treated Patients

Abstract: In this report we have described three patients with chronic schizophrenia on long-term chlorpromazine therapy who developed asymptomatic IgM inhibitors of the intrinsic phase of blood coagulation. The anticoagulant resulted in decreased measurements of all of the plasma clotting factors in the intrinsic pathway (factors VIII, IX, XI, XII, Fletcher factor and Fitzgerald factor). Using crude coagulation reagents, the serum of these patients interfered with the clot promoting activity of contact product. To dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…Interaction of activated macrophages, complement, and immunoglobulins leads to destruction of T. gondii with release of Toxoplasma and cellular debris (6). This damaged cell debris may act as immunosuppressive products and stimulate suppressor T-lymphocytes (7), which block the reaction of responder T-lymphocytes (8). (B) Phospholipid glycoprotein complex from damaged cells activates factor VII and thus the extrinsic pathway of blood coagulation (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction of activated macrophages, complement, and immunoglobulins leads to destruction of T. gondii with release of Toxoplasma and cellular debris (6). This damaged cell debris may act as immunosuppressive products and stimulate suppressor T-lymphocytes (7), which block the reaction of responder T-lymphocytes (8). (B) Phospholipid glycoprotein complex from damaged cells activates factor VII and thus the extrinsic pathway of blood coagulation (9).…”
Section: Discussionmentioning
confidence: 99%
“…To demonstrate the specificity of the inhibitor, assays of factors V, VIII, IX, X, XI, and XII were performed on mixtures of normal plasma and dilutions of patient's plasma. Detection of an inhibitor of the contact phase of blood coagulation was according to Zucker et al 8 The inhibitory effect was quantified by comparing the clotting time of the patient's plasma with a dilution curve of contact factors. Neutralisa-tion of the circulating anticoagulant was performed using rabbit anti-human ,s chain and y chain antisera (Dako, Copenhagen).9…”
Section: Coagulation Studiesmentioning
confidence: 99%
“…One year later, Zucker et al [40] were the first to describe elevated serum IgM levels in chlorpromazine-induced LA (CPZILA). Additionally, they demonstrated that the IgM fraction was responsible for the LA activity.…”
Section: Phenothiazinesmentioning
confidence: 99%
“…Chlorpromazine is the most frequent culprit with over 300 cases reported [14,18,31,32,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. The first report of a phenothiazine-induced LA (PZILA) was published in 1977 by Canoso and Hutton [39].…”
Section: Phenothiazinesmentioning
confidence: 99%
“…AHA has been associated with malignancy, autoimmune disorders, pregnancy, multiple transfusions, or no apparent disease [3]. Inhibitors against other clotting factors are much rarer [1]; in particular those against FXI have been only anecdotally reported [412]. …”
Section: Introductionmentioning
confidence: 99%